Indicações geográficas do Amapá: mestria das louças produzidas no quilombo do Maruanum - NEVES, Lúcio Dias das (2020)
This final report presents the activities carried out between September 2018 and December 2019, in the Professional Master's Program in Intellectual Property and Technology Transfer for Technological Innovation (ProfNIT / UNIFAP), the propositional diagnosis was about the claim of the Geographical Indication request with the INPI, for recognition / notoriety about the production process of vitreous china from the Maruanum quilombo, a district located in the rural area of Macapá. This is the case study through observatory research and documentary analysis with bibliographic review - with secrecy rules, on the production process of the dishes made by quilombola women from Maruanum, rural area of the city of Macapá, normative instruction 095 / 2018, guides that the Indication of Origin is essentially linked to the renown (tradition of production, extraction, production, manufacturing). That said, the traditional process and techniques for the production of Maruanum vitreous chinaware have such characteristics because they are unique / singular in the Amazon region, and that (re) there is an ancient ancestral ritual for extracting the raw material in harmony with the environment, respect for the soil, as well as the initial selection process on who / which pottery is suitable for this moment of collection, the mystique with nature, and even the depth and location from which this clay is removed, with a view to the possibility of IG request from INPI.